Non-alcoholic fatty liver disease: a practical approach to treatment. Issue 4 (22nd January 2014) - Dyson, J K; Anstee, Q M; McPherson, S
Abstract : Non-alcoholic fatty liver disease (NAFLD) affects up to a third of the population in many developed countries. Between 10% and 30% of patients with NAFLD have non-alcoholic steatohepatitis (NASH) that can progress to cirrhosis. There are metabolic risk factors common to both NAFLD and cardiovascular disease, so patients with NASH have an increased risk of liver-related and cardiovascular death. Management of patients with NAFLD depends largely on the stage of disease, emphasising the importance of careful risk stratification. There are four main areas to focus on when thinking about management strategies in NAFLD: lifestyle modification, targeting the components of the metabolic syndrome, liver-directed pharmacotherapy for high risk patients and managing the complications of cirrhosis.